Effects of Exhaustive Exercise on Peripheral Blood Lymphocytes - Ja’afar, Israa F.; Abid, Balsam F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Acute exercise stress is associated with a lower lymphocyte functional response. It is suggested that exercise can enhance or reduce immunity depending on the frequency, duration, and intensity of the exercise. Subjects and Methods: From November 2007 to January 2008, thirty healthy Volunteers were recruited from medical, paramedical staffs, and students of Baghdad College of Medicine (all males). Participants were chosen according to the following: (1)Age (between 20 and 35 years), (2) Non obese : Body mass index (BMI in kg/m2) was used as an index of obesity, (3) Non-smoker, (4) No recent medical problem, (5) No recent medications, and (6) No musculoskeletal complaint. After a general medical checkup, the thirty subjects were subjected to the exercise protocol. Blood samples were taken before, and immediately after the end of exercise. Results: The mean age of individuals enrolled in the study was 29 ± 4years. Exercise induced significant granulocytosis whereas lymphocytes declined to a level significantly below the baseline. Trypan blue exclusion test showed that the initial percentage of nonviable lymphocytes was 2.90% ± 0.2%. After exhaustive exercise, cell viability decreased where percentage of nonviable cells was 4.3% ± 0.3% (p<0.005). Early apoptotic lymphocytes showed membrane blebbing and did not take the dye, while dead cells appeared blue from dye uptake. MDA was 3.0 ± 0.23 nmol/ml. An increment in the mean value of MDA was observed in the post exercise blood sample that was withdrawn immediately after exercise (p<0.005). Conclusion: The present study shows that exhaustive exercise induces apoptosis in peripheral blood lymphocytes manifested by increased level of malondialdehyde, an oxidative stress marker. This finding supports the hypothesis that apoptosis could be involved in exercise-induced lymphocytopenia and this effect depends on exercise intensity.